Pengaruh P53 Dan YY1 Terhadap Terjadinya Kanker Serviks - Jacobus Jeno Wibisono (Medicinus, 2018)
Cervical cancer is one of the most prevalent cancer in the world and caused by Human Papilloma Virus (HPV). The pathogenesis of cancer as whole (50%) is caused by gene mutation. HPV stimulates carcinogenesis on cervix epitel cells by HPV-Encoded viral oncoproteins, E6 and E7, which will inhibit tumor suppressor gene activation, such as p53 gene. HPV-encoded E6 oncoprotein  is able to directly attached on p53 causing degeneration via E6-AP-mediated ubiquitination pathway. Moreover, overexpression on YY1 gene has significant role on the progression of HPV on cervical cancer. YY1 inhibits p53 activation dan inhibits apoptosis on cells infected by HPV. Overexpression of YY1 induces reduction of endogenous p53, which will inhibit p53 function as tumor suppressor gene.Keywords: cervical cancer, HPV, P53, YY1